Hospital Pharmacists’ Attitudes Concerning Antibiotic Resistance: A Pilot Study - Roque, Fátima (2016)
The World Health Organization has defined antimicrobial resistance as one of the main concerns of public health for the next years. This study sought to evaluate a questionnaire’ reproducibility and internal consistency about attitudes and knowledge of pharmacists working in hospital pharmacy concerning antibiotic use and bacterial resistance.